Histological Alterations in the Body Wall of the Tropical Earthworm Eudrilus eugeniae Exposed to Hexavalent Chromium - Fernando, V. K.; Perera, Inoka C.; Dangalle, C. D.; Premawansa, S.; Wijesinghe, M. R. (My University, 2015)
The tropical earthworm Eudrilus eugeniae was chronically exposed to hexavalent chromium (Cr) in its substrate over a concentration range from 0.24 to 893 mg kg-1 . Histological alterations in the body wall epithelium included cell fusion, reduction in thickness of the epithelial layer, a marked increase in pyknotic nuclei and epithelial sloughing. Similar changes were noted in the circular and longitudinal muscles with damage being indicated by the prominent inter-muscular cell spaces and disintegration. Many of these noted alterations intensified with increasing levels of exposure. It is significant that some of the changes recorded here were evident even at the lowest concentration of 0.24 mg kg-1 , an environmentally relevant concentration. Hence, the observed trends could be taken as an early warning to the imminent threats of heavy metal pollution to epigeic earthworm species.
Keywords: Earthworms, Heavy metal, Histology, Pollution, Toxicity